Switching control approach for stable navigation of mobile robots in unknown environments - Toibero, Juan Marcos (2011)
This paper presents a stable switching control strategy for the parking problem of non-holonomic mobile robots. First, it is proposed a positioning-orientation switching controller for the parking problem. With this strategy robot backwards motions are avoided and the robot heading is always in the direction of the goal point facilitating the obstacle handling. Second, the avoidance of unexpected obstacles is considered in a reactive way by following the contour of the obstacles. Next, the stability of the switching parking/obstacleavoider controller is analyzed showing stability under reasonably conditions. Finally, the good performance and the feasibility of this approach are shown through several experimental results.